2017
DOI: 10.3390/scipharm85030033
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Composition of the Essential Oils and Biological Activities of Angelica Species

Abstract: A number of Angelica species have been used in traditional systems of medicine to treat many ailments. Especially, essential oils (EOs) from the Angelica species have been used for the treatment of various health problems, including malaria, gynecological diseases, fever, anemia, and arthritis. EOs are complex mixtures of low molecular weight compounds, especially terpenoids and their oxygenated compounds. These components deliver specific fragrance and biological properties to essential oils. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…Sowndhararajan et al reported that there are differences in major components depending on the plant part, yield, and extraction method in essential oil of various species of Angelica [ 32 ]. Therefore, to clarify the major components and biologically active components of the AGN extract, the AGN extract was divided into eight fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Sowndhararajan et al reported that there are differences in major components depending on the plant part, yield, and extraction method in essential oil of various species of Angelica [ 32 ]. Therefore, to clarify the major components and biologically active components of the AGN extract, the AGN extract was divided into eight fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial infestation is a major cause of food spoilage. It has been reported that AEO has effective and broad-spectrum antibacterial activity, which could be related to ligustilide, one of the main compounds of AEO [35]. The antibacterial activity of gelatin/AEO nanofibers tested by semi-quantitative shake flask method is presented in Figure 7.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Essential oils are able to counteract free radicals and anti-inflammatory agents against oxidative explosions [23]. The content of terpene compounds in essential oils of canarium tree resin that is β-phellandrene, α-phellandrene, γ-terpinene and ρ-cymene are reported to provide anti-inflammatory properties by inhibiting migration and decreasing the production of inflammatory mediators, including protease and proinflammatory enzymes such as COX-1 and COX2 [24]. αphellandrene significantly decreases mast cell degranulation in regulating the inflammatory response.…”
Section: Effects Of Resin Essential Oils Of Canarium Tree On Proteasementioning
confidence: 99%